PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE DENGAN VARIABEL INTERVENING EMPOWERMENT DAN CUSTOMER SATISFACTION PADA SEKTOR PERBANKAN DI SURABAYA - Melina Andriani (Business Accounting Review, 2016)
The purpose of this study was to know whether there was significant affect of Leadership Style towards Financial Performance through Empowerment and Customer’s satisfaction as intervening variables in banking corporate in Surabaya. The sample used in this study was banking corporate listing on Bursa Efek Indonesia (BEI) that generate profit in the last 3 years. Data analysis used Partial Least Square method with 600 respondents from 30 selected banks in Surabaya. The result of this study showed that Leadership Style had positive affect on Financial Performance.